Black narcissus [videorecording (DVD)] - Powell, Michael, 1905-1990; Pressburger, Emeric, 1902-1988; Kerr, Deborah, 1921-2007; Sabu, 1924-1963; Farrar, David, 1908-1995; Robson, Flora, 1902-1984; Knight, Esmond, 1906-1987; Simmons, Jean, 1929-2010; Godden, Rumer, 1907-1998 (Criterion collection, 2000)
Majesty gives way to mystery, and marks a harrowing descent into madness, when a young British nun is ordered to establish a convent in the remote Himalayan mountains. Sister Clodagh (Kerr) is a serious young novitiate assigned to lead a crucial mission, with the reluctant recommendation of her Mother Superior. Together with a disparate group of nuns, Sister Clodagh will face strange peoples and customs, a harsh and unforgiving climate and a wrenching struggle with her own past that will prove the ultimate test of her devotion and faith.